2020
DOI: 10.1177/000313482008600336
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Recurrent Paraesophageal Hernia Repair with Roux-en-Y Gastric Bypass

Abstract: Roux-en-Y gastric bypass (RYGB) has been explored as a revisional option to failed paraesophageal hernia (PEH) repair with fundoplication, particularly in patients suffering from obesity. However, few studies have assessed long-term outcomes of RYGB with revisional PEH repairin regard to acid-suppressing medication use. We retrospectively identified 19 patients who underwent revisional PEH repair with RYGB between 2011 and 2018. The median operative time was 232 minutes with a median hospital length of stay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In our study, the complication rate for ARGB was similar, but slightly higher, to that of standalone fundoplication, which is reported in the literature between 6% and 26% [13,22,23]. A recent study examining hiatal hernia repair and RYGB, but not massive hiatal hernias, found a complication rate of 26.3% within one year of surgery [17]. Perioperative outcomes for hiatal hernia repair with RYGB, such as overall morbidity, have been reported in the literature between 6.2% and 9.0% [24,25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the complication rate for ARGB was similar, but slightly higher, to that of standalone fundoplication, which is reported in the literature between 6% and 26% [13,22,23]. A recent study examining hiatal hernia repair and RYGB, but not massive hiatal hernias, found a complication rate of 26.3% within one year of surgery [17]. Perioperative outcomes for hiatal hernia repair with RYGB, such as overall morbidity, have been reported in the literature between 6.2% and 9.0% [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in comparison to a relatively high radiographic recurrence rate between 15% and 66% for standard PEH repair with fundoplication, although symptomatic recurrence is lower [13][14][15][16]. Other studies have examined recurrence in the setting of hiatal hernia repair and gastric bypass but not in the setting of massive hiatal hernias [17,18]. Our ability to detect recurrences is limited by the relatively short mean follow-up, and studies with longer follow-up and regular imaging will be needed to fully characterize the rate of recurrence in this population.…”
Section: Discussionmentioning
confidence: 83%
“…In morbidly obese patients, there is already consensus that a bariatric procedure should be added to the hernia correction. Roux-en-y gastric bypass is the recommended technique because it presents better results in treating reflux, with good weight loss, control of comorbidities, and reduction of LHH recurrences 43 .…”
Section: Special Situationsmentioning
confidence: 99%